The effect of a period of resistance training on Thrombosponidine-1 and Follistatin-like-1 in heart tissue of obese male rats - Neda Ghasemi; Mania Roozbayani; Hossein Shirvani (فیزیولوژی ورزش و فعالیت بدنی)
Background and Purpose: Physiological angiogenesis and homeostasis of blood vessels is a complex process that is regulated at a high level by the balance between positive proteins such as follistatin-like factor-1 (FSTL-1) and negative proteins such as thrombospondin-1 (TSP-1). Although, there is considerable evidence about the role of positive factors in angiogenesis, the role of negative factors is not well defined. In physiological conditions, such as resistance training as one of the effective training methods to improve cardiovascular function, the role of these factors is not properly known. The aim of this study was to investigate the changes in thrombospondin-1 and follistatin-like factor-1 of heart tissue following six weeks of resistance training in obese male rats. Materials and Methods: In an experimental study, 20 male Wistar rats were divided into two equal groups of control and experimental based on their body weight. Prior to the exercise protocol, the rats received a high-calorie diet. The experimental group participated in a six-week training protocol with a frequency of three training sessions per week, and each session included 10 repetitions with a 90-second rest interval, climbing a resistance training ladder with a height of one meter and an 85-degree incline with a weight attached to the base of the tail (based on the the maximum weight carrying capacity of each rat). Fourty-eight hours after the last training session, TSP-1 and FSTL-1 values in the heart tissue were evaluated using ELISA technique. Between-group comparisons were made by using the independent t-test at a significance level of P<0.05. Results: Data analyses revealed that six weeks of resistance training in the experimental group compared to the control group caused a significant increase in FSTL-1 values (P=0.0001) and a non-significant decrease in TSP-1 values (P=0.09). Conclusion: Based on the findings of the present study it could be concluded that exercise in the form of resistance exercises can have positive effects on the development of angiogenesis process in heart tissue and it seems that six weeks of resistance training, despite the non-significant decrease in TSP-1 as an inhibitory factor in the angiogenesis process and an increase in FSTL-1 values as an angiogenesis stimulating factor, may have positive effect on improving blood supply to the heart muscle in obese subjects. The data of the present study refer to the role of resistance training in facilitating intracellular signaling through, modulating some inhibitory factors and stimulatory factors of angiogenesis in heart tissue of obese rats.